(untitled) (African Journal of Biomedical Research, 2022)
This study was designed to investigate the effects of cortisol on lipolysis in the common African toad Bufo regularis. Adult toads were collected and used for the study. The animals were fasted 24h and anaesthised by sodium thiopentone 50mg/kg intraperitoneally. Blood was collected from truncus arterious for estimation of blood glucose and blood free fatty acids levels. Cortisol caused significant increase in blood free fatty acids and glucose levels in the common African toad. Pretreatment with prazosin 0.2mg/kg produced significant reduction in blood free fatty acids but caused increase in blood glucose levels. Propranolol 0.5mg/kg pretreatment caused significant increase in blood free fatty acids and significant reduction in glucose levels. The combination of both blockers abolished the cortisol-induced hyperglycemia and caused significant reduction in blood free fatty acids. The results of this study confirmed that cortisol caused lipolysis from toad adipose tissue. Thus, cortisol administration caused increase in plasma free fatty levels and induced hyperglycemia. The alpha-adrenergic receptors are involved in the release of free fatty acids in the common African toad bufo regularis